Effectiveness of Mail Management in the Office of the Governor of South Sulawesi Province - Muh. Darwis; Nur Afifah; Sitti Arhas (Asha Publishing, 2024)
Mail management affects the effectiveness of correspondence because the creation of effective mail management will help organizations organize and find letters or documents needed quickly so as to increase operational efficiency in the organization. This study aims to determine the Effectiveness of Mail Management in the Office of the Governor of South Sulawesi Province, especially in the General Subdivision of BKAD (Regional Finance and Assets Agency). Therefore, research has significant in identifying factors or barriers that affect effectiveness in mail management. This research is qualitative, therefore, to achieve the objectives of the study, data collection techniques are used, namely observation, interviews and documentation. The results showed that mail management in the general subdivision of BKAD of the South Sulawesi Provincial Governor's Office consisted of incoming mail management which included 1) Mail receipt; 2) Mail sorting; 3) Recording of letters; 4) Mail briefing; 5) Mail processing; 6) Mail storage. Outgoing mail management includes 1) Drafting letters; 2) Signing of letters; 3) Mail delivery; and 4) Archive storage. This is in accordance with the procedure so that it can be said to be effective. In the process of managing mail, there are still obstacles such as 1) Manual mail management; and 2) Clerical errors. Efforts to overcome these obstacles 1) Propose that mail management be carried out with an electronic mail management system or e-mail; and 2) Attend special training conducted by agencies related to the management of correspondence. This study presents new information by linking detailed theories and research loci different from previous research on the effectiveness of mail management so that it can be used as evaluation material for research loci to increase effectiveness in managing mail